Five-Level Multiple-Pole PWM AC-AC Converters with Reduced Components Count - Lim, Ziyou (2016)
This paper proposes novel multilevel AC/DC/AC converters with reduced number of semiconductor devices to achieve light weight, efficiency and better input current quality. The proposed three-phase front-end bidirectional five-level (5L) rectifier and rear-end 5L-inverter are constructed based on multiple-pole multilevel diode-clamped approach (M2DCC), which consist a total number of 24 diode components clamped. Based on M2DCC concept, the number of switching devices can be further reduced to construct a new unidirectional front-end rectifier (M2SCR). Comparative studies are conducted to analyze the performances of the two proposed front-end rectifiers with supportive mathematical derivations. Experimental prototypes have proven the feasibility of the proposed AC/DC/AC configurations. Results obtained show that low current harmonic distortions of 5% and high power factor of 0.99 are achieved with small input inductors despite of low switching frequency operation at 1 kHz.